ACTIVE METHODOLOGIES IN PROFESSIONAL AND TECHNOLOGIAL EDUCATION: systematic review of the literature (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2022)
The present study, developed within the scope of the Specialization Course in Teaching in the Professional Education at the Federal Institute of Alagoas, sets out to carry out a Systematic Literature Review (SLR) of research carried out in the last five years (2017-2021), in Brazil, available in the Brazilian Digital Database of Theses and Dissertations, which present as objects of investigation the Active Learning Methodologies applied to Professional and Technological Education, and with that, contribute with the knowledge about the insertion, or not, of the Active Learning Methodologies in the Professional and Technological Education (PTE). For this, we carried out a theoretical dialogue on Active Learning Methodologies and their relationship with professional education and discussed some of the active methodologies that were revealed in the research data, they are: problem-based learning, project-based learning, classroom inverted, among others. It was an SRL-type research with a quantitative-qualitative approach. The results showed that although there was a significant number of works carried out in the last five years that had active methodologies as their object of investigation, only 17 of them were carried out within the scope of the EPT. This leads us to infer that there is a gap in studies aimed at this relationship. This reveals the need for greater engagement in the scientific community regarding the study of such methodologies within the scope of the PTE.
Keywords: Professional and Technological Education (PTE); Active Learning Methodologies; Systematic Literature Review (SLR)